Therapeutic effect of intraductal irrigation of the salivary gland: A technical report - Lee, Chena; Kim, Jo-Eun; Huh, Kyoung-Hoe; Yi, Won-Jin; Heo, Min-Suk; Lee, Sam-Sun; Choi, Soon-Chul (Imaging science in dentistry, 2017)
Obstructive and inflammatory disease often occurs in the major salivary glands, and no predictive treatment has yet been developed for this condition. The aim of this report was to introduce an intraductal irrigation procedure and to illustrate its application to practical patient cases. Two patients complaining of pain and swelling in the parotid gland during meals who underwent sialography were diagnosed as having sialodochitis with sialadenitis. Intraductal irrigation was then performed on the parotid gland on the side of the complaint. The irrigation procedure was conducted in the same manner as the sialography procedure, except that saline was used as the filling solution. Symptom severity was evaluated with a numerical rating scale (NRS) at the initial visit and a month after the irrigation. The initial NRS value of patient 1 was 10. The value decreased to 6 and then to 0 after 2 irrigation procedures. The NRS value of patient 2 regarding the symptoms involving the left parotid gland decreased from 4-5 to 1 after 4 irrigation procedures performed at 1-month intervals. Intraductal irrigation of the salivary gland may be a simple, safe, and effective treatment option for patients with obstructive and inflammatory disease of the salivary gland that is capable of resolving their symptoms.